Love, War and the Grail - Nicholson, Helen J., author.
1 online resource.
Keywords: This is a study of the appearances of the Knights Templar, Knights Hospitaller and Teutonic Knights in the French, German and English epic and romance literature of the Middle Ages. It examines their religious roles, such as caring for the sick, their warrior role of fighting Muslims, and examines the role of 'Templars' in the Grail romances. It traces how these roles developed over time and considers what function the appearances of these military religious orders performed in the composition of a work of fictional literature. The frequent appearances of the Military Orders in medieval fictional literature are of interest both to historians and to literary specialists. This is the first study to consider the subject in depth across the medieval period.